Effects of solar irradiation on the properties of ethylene-norbornene composites containing solvent dyes. (September 2017) - Marzec, Anna; Boruszczak, Zygmunt; Rogowski, Jacek; Zaborski, Marian
Abstract: This study investigates the effects of irradiation with artificial solar light on the resistance to aging of ethylene-norbornene (EN) copolymer with different solvent dyes and commercial stabilizers. The mechanical properties of the samples were measured before and after ageing using tensile tests. FTIR spectroscopy was used to evaluate the carbonyl index as a measure of photooxidation after irradiation. It was found that the carbonyl index of the samples depended on the type of additive in the composite. Secondary ion mass spectrometry (TOF-SIMS) was used to analyze the chemical composition of the sample surfaces. The degree of oxidative aging was evaluated by measuring the intensities of secondary Cx Hy Oz + type ions. Samples containing anthraquinone solvent dyes, such as Solvent Blue 97 or Solvent Green 28, showed the most significant improvements in durability in an aging test. Some of the applied solvent dyes showed much greater ability than the studied stabilizers to protect EN films exposed to the full solar spectrum.